Drug Delivery by Carbon Nano Carrier for Use as Capecitabine Drug Carrier: A QM/MM study - Fahimeh Najafi (Nanochemistry Research, 2025)
The most important and common methods of cancer treatment are chemotherapy, surgery and radiotherapy. But these mentioned methods have important side effects such as intolerable toxicity, limited drug access to cancer cells, heterogeneous drug and biological resistance of growing cancer cells, which reduce success rate. Therefore, there is urgent need to use drug delivery systems and targeted treatment to improve the treatment process. The use of single-walled carbon nanotubes is a targeted cancer treatment. The aim of this project is to investigate different variables on interaction potential of anticancer drug as an anticancer agent with single-walled carbon nanotubes. Interaction bond energy values were evaluated and corrected by basis set superposition error (BSSE) in the M06/6-311+G* level. The evaluated results showed that by increasing dielectric constant of the solvent, the bonding energy decreases. Consequently, the stability increases. Then the evaluated results of interaction of SWCNT with the capecitabine drug at the M06/6-311+G* level state that this absorption is spontaneous. According to the results of AIM analysis, the N1—C87 interaction bond has a partial covalent nature. The transition electron can migrate from the donor atom (the lone pair of nitrogen in capecitabine) to the σ^*-orbital of the acceptor atom (the σ^*orbital of carbon atom of SWCNT), as observed and reported by NBO analysis. Monte Carlo simulation results showed that the solvation free energy in water solvent becomes more negative due to the interaction between the anticancer drug with SWCNT. The total energy of the resulting complex of interaction was more negative than that of SWCNT, indicating that both methods corresponded with each other.